Endocrine dysregulation in COVID-19: molecular mechanisms and insights - Iosef, Cristiana; Matusa, Andrei M.; Han, Victor K. M.; Fraser, Douglas D. (Frontiers in Endocrinology, 2024)
This review describes the impact of COVID-19 on the endocrine system, focusing on cortisol signalling and growth factor-induced endocrine resistance. As expected, SARS-CoV-2 infection induces systemic inflammation resulting in stimulation of the adrenal glands leading to elevated cortisol levels with normal adrenocorticotropic hormone (ACTH) levels. The cytokine storm could also stimulate cortisol production. However, in some instances, cortisol levels rise independently of ACTH due to a phenomenon known as "pseudo-Cushing's syndrome," where adrenal glands become less responsive to ACTH. Plasma proteomic analyses showed that this pattern was variably observed among COVID-19 patients, potentially involving calcium dysregulation and GNAS-regulated activities, ultimately impacting the regulation of vascular permeability. COVID-19 also exhibited a syndrome resembling endocrine resistance, governed by receptor tyrosine kinase signalling pathways. Mild cases displayed elevated activity of EGFR and MMP9, along with increased expression of survival factors like Bax and Bcl2. In contrast, more severe cases involved IGFR-I and enhanced NOTCH signalling, with altered expression of Bcl2, AKT1, and MAPK8. In summary, these findings describe the complex interplay between COVID-19 and endocrine pathology, particularly endocrine resistance. These insights suggest potential endocrine targets for therapeutic interventions to improve short-and long-term outcomes for COVID-19 patients.